Evaluasi Pengelolaan Sumber Daya Manusia dan Manajemen Operasional Menggunakan Framework COBIT 5 (Studi Kasus: Dinas Komunikasi dan Informatika Kabupaten Lumajang) - Aminah Rokhikim Makhtum; Widhy Hayuhardhika Nugraha Putra; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika (Dinas Kominfo) Kabupaten Lumajang is one of the government agencies that is tasked with serving the community in the field of information and communication. Some of the services managed by the Dinas Kominfo include intranet development services and the use of internet access, data center infrastructure services, e-Govenment data and information management services, e-Government information security services, and integration of government public services. To manage these services needed adequate human resources (HR) for the implementation of operational activities properly. Based on the results of interviews, it is known that the condition of human resources at the Dinas Kominfo is still lacking which causes an overwork with the many operational activities related to information technology at Diskominfo. Therefore an evaluation is needed to determine the current condition of HR management and operational management processes at Diskominfo so that recommendations can be given on existing problems. The evaluation is based on the COBIT 5 framework of APO07 (Manage Human Resource) and DSS01 (Manage Operations) processes. Data were collected by several methods, namely interviews, questionnaires, and observations. The assessment is carried out in stages starting from level 0 to level 5 to determine the level of capability. Capability level obtained in each process is level 1 with a gap of 1 from the target level. Recommendations that can be given for the APO07 process are 10 points and for DSS01 are 6 points.